Study of two types of protein-protein interactions : i, a high affinity antigen-antibody complex and ii, a transient complex between an oncoprotein and a methyltransferase - Tambe, Anagha (2018)
Protein-protein interactions together constitute the complex fabric of biochemical circuitry that drives the physiological functions. This tinkering network is controlled in part by the nature of affinity of these interactions. Some interactions demonstrate strong affinity and most are of transient nature with weak affinity. In this work we describe two such interactions. One interaction is between a broad-spectrum antibody (m366.6) with neutralization capacity for all four Dengue serotypes. This is a very strong interaction with KD value in nanomolar range. The antigen of this antibody is situated in third last domain of Dengue envelope (ED III). We tried to analyze the complex of this interaction with crystallography with the aim of exploring the atomic structure to facilitate engineering better antibody for passive immunotherapy and / or better antigen as a potential candidate for vaccine against flavivirus. With this perspective we also analysed a consensus domain III engineered to have optimum similarity with all four Dengue serotype ED IIIs. It being thermostable we tested it further as a potential vaccine candidate through a novel mode of delivery by Micro-needles. We tested its affinity for cross-protective antibody Ab 513 by SPR. Lastly, we also checked ability of m366.6 to neutralize Zika virus. We also analyzed the atomic structure of Consensus EDIII by X-ray crystallography to analysze its conserved fold. The second interaction is of transient type of 0.1μm KD between two proteins Vav1, a GDP/GTP exchange factor and Ezh2, a polycomb group Histone methyltransferase. Reports indicate involvement of this interaction in mobilization of hematopoietic cells by influencing the adhesion dynamics through integrin pathway. This is implicated in transformation of cells. Abolishing this interaction could be a mode of treatment for such cellular transformation. We in our work tried to identify the residues involved in this interaction NMR. Currently, we have solved individual structure of the Ezh2 construct by NMR and co-crystallization.